PENGARUH STRES KERJA, LINGKUNGAN KERJA, DAN KEBIJAKAN KEHIDUPAN KERJA TERHADAP TURNOVER INTENTION PADA RUMAH SAKIT DI KOTA JAKARTA PUSAT - Setiawan, Shirleena; Pauline H Pattyranie Tan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study was to examine whether 1) There is an influence between work stress on turnover intention at a Hospital in Central Jakarta, 2) There is an influence between the work environment on turnover intention at a Hospital in Central Jakarta, 3) There is an influence between work life policies on turnover intention in hospitals in Central Jakarta. The selected sample amounted to 150 respondents nurses in hospitals in Central Jakarta. The results show that there is a significant positive effect between work stress and work environment on turnover intention. Furthermore, the next finding is that there is no positive influence between work life policies on turnover intention.